Study of College of Engineering facilities for microconcrete structural models analysis - Suthdatumprapah, Pinij
This research is divided into two aspects. The first aspect is to ascertain whether the facilities, of the College of Engineering, University of the Philippines, are adequate for fabrication and testing of structural reinforced microconcrete models. The second aspect consists of making and testing the models.